Visual representation of the historical city in digital media - Olga Shirokova (Urbis et Orbis: Mikroistoriâ i Semiotika Goroda, 2024)
The article analyses the visual representation of the historical city in digital media as one of the leading ways of urban identity. The author shows that the connection of the image with the city, which is a territorial carrier of visual and symbolic information, and with city digital representation is established and coordinated with the help of an intermediary – digital media, including social networks. On the example of Veliky Novgorod, it is investigated how the image of the city in the media environment shapes the idea of the real urban space for most Internet users. The article identifies the main elements of urban space that emphasize Veliky Novgorod’s status as a historical city: cultural-historical and natural landscape. The visual representation of the historic city emphasizes the uniqueness of a place and expresses local identity, which allows one to distinguish a certain urban space in the endless flow of visual data. At the same time, the author notes that digital media do not display the entire urban space, but only the part that is recorded and then actively disseminated by Internet users. Such incompleteness of the visual representation of the historical city provokes the emergence of socio-cultural distortions: the reproduction of basic visual patterns works to form a stereotypical image that does not reflect the heterogeneity of the real urban environment.